Predicting outcome after cardiac resynchronisation therapy defibrillator implantation: the cardiac resynchronisation therapy defibrillator Futility score. Issue 15 (11th April 2022) - Maille, Baptiste; Bodin, Alexandre; Bisson, Arnaud; Herbert, Julien; Pierre, Bertrand; Clementy, Nicolas; Klein, Victor; Franceschi, Frédéric; Deharo, Jean-Claude; Fauchier, Laurent
Abstract : Background: Risk-benefit for cardiac resynchronisation therapy (CRT) defibrillator (CRT-D) over CRT pacemaker remains a matter of debate. We aimed to identify patients with a poor outcome within 1 year of CRT-D implantation, and to develop a CRT-D Futility score. Methods: Based on an administrative hospital-discharge database, all consecutive patients treated with prophylactic CRT-D implantation in France (2010–2019) were included. A prediction model was derived and validated for 1-year all-cause death after CRT-D implantation (considered as futility) by using split-sample validation. Results: Among 23 029 patients (mean age 68±10 years; 4873 (21.2%) women), 7016 deaths were recorded (yearly incidence rate 7.2%), of which 1604 (22.8%) occurred within 1 year of CRT-D implantation. In the derivation cohort (n=11 514), the final logistic regression model included—as main predictors of futility—older age, diabetes, mitral regurgitation, aortic stenosis, history of hospitalisation with heart failure, history of pulmonary oedema, atrial fibrillation, renal disease, liver disease, undernutrition and anaemia. Area under the curve for the CRT-D Futility score was 0.716 (95% CI: 0.698 to 0.734) in the derivation cohort and 0.692 (0.673 to 0.710) in the validation cohort. The Hosmer-Lemeshow test had a p-value of 0.57 suggesting accurate calibration. The CRT-D Futility score outperformed the Goldenberg and EAARN scores for identifying futility. Based on the CRT-D Futility score, 15.9% of these patients were categorised at high risk (predicted futility of 16.6%). Conclusions: The CRT-D Futility score, established from a large nationwide cohort of patients treated with CRT-D, may be a relevant tool for optimising healthcare decision-making.